Pengaruh Kepemimpinan Transformasional terhadap Kinerja Karyawan melalui Otonomi Kerja - Ramadhani, Muhammad Alief; Indawati, Nurul (Jurnal Ilmu Manajemen, 2021)
This research aims to explore the effect of transformational leadership on employee performance mediated by job autonomy at CV SKM Indonesia. During this yearly pandemic, job autonomy is applied in CV SKM Indonesia conceived by the work from the home method. Quantitative methods are chosen to process the questionnaire employees filled in—collecting 34 respondents as a total population from multiple divisions in CV SKM Indonesia and using multiple linear regression from SPSS PASW18 software for an analytical tool. This study verifies the positive and significant effect between transformational leadership and employee performance mediated by job autonomy as an intervening variable. This study shows that the practice of transformational leadership from the leader of the company is going well, and employee also has an excellent job autonomy on their self and that is helping them increasing performance to complete their job in the company. The company should let the employee make a monthly evaluation and keep improving their new work system to increase their performance.